An Unusual Case of a Perforated Meckel’s Diverticulum - Lybil Mendoza Alvarez; Dhanashree Rajderkar; Genie L. Beasley (Case Reports in Pediatrics)
Background. Meckel’s diverticulum, the most common congenital anomaly of the gastrointestinal tract, typically presents in children with gastrointestinal bleeding. Case Presentation. An 11-year-old Caucasian male presented with a 6 week history of abdominal pain, vomiting, and diarrhea. He was found to have iron deficiency anemia, markedly elevated serum and fecal inflammatory markers, and imaging showing a contained bowel perforation. He was evaluated for infectious etiologies and later underwent extensive testing for inflammatory bowel disease. Ultimately, he was found to have a Meckel’s diverticulum, which was successfully resected and led to resolution of his gastrointestinal complaints. Conclusions. This case report highlights one of the more rare presentations in children, which is intestinal perforation. Symptoms of a Meckel’s diverticulum can overlap with those of inflammatory bowel disease, as demonstrated by our patient. Clinicians should be familiar with criteria to establish diagnosis of inflammatory bowel disease, and if diagnosis isn’t fully supported by testing, they should expand the differential and consider Meckel’s diverticulum.